THE ROUTINE USE OF THE METHYLENE BLUE TEST IN SLEEVE GASTRECTOMY: WHY NOT? - FERRAZ,Álvaro A. B. (2021)
ABSTRACT Background: Although considered a safe procedure, sleeve gastrectomy (SG) has a non-negligible risk of major postoperative complications related to it, with special attention to gastric leaks. Aim: Evaluate the clinical value of the methylene blue test (MBT) in predicting the occurrence of post-SG leaks. Methods: Retrospective study that included 1136 patients who underwent SG with intraoperative MBT between 2012 and 2016. Sensitivity, specificity, positive predictive value (PPV) and negative predicted value (NPV) were calculated to determine the clinical correlation between the MBT and the occurrence of postoperative leaks. Staple line oversewing was performed in all patients who presented positive MBT. Results: Laparoscopic SG was performed in 97.0% of cases; open in 2.3%, and robotic in 0.7%. MBT was positive in 19 cases (1.67%). One positive MBT occurred during an open SG and the other 18 at laparoscopy. Moreover, there were nine cases (0.8%) of postoperative leaks, among which, only two presented positive MBT. MBT diagnostic value was evaluated through the calculation of sensitivity (22.0%), specificity (98.0%), PPV (11.0%) and NPV (99.0%). There were no cases of allergic reaction or any other side effect with the use of the methylene blue solution. Conclusion: MBT showed high specificity and negative predictive value, thus presenting an important value to rule out the occurrence of postoperative leaks.